Platelet rich plasma (PRP) in the surgical treatment of Haglund’s syndrome: the use of PRP membranes as an intra-operative local adjuvant - Giuseppe Restuccia; Giorgio Varchetta; Alessandro Lippi; Lorenzo Dolfi; Federico Bizzocchi; Stefano Giovannetti; Edoardo Ipponi (Medicinski glasnik, 2023)
Aim: Haglund's syndrome may be responsible for chronic pain in the ankle and hindfoot. Although numerous therapeutic approaches have been described in the literature, to this date no consensus over a surgical treatment has been established. We report our experience in the treatment of Haglund's syndrome and pre-insertional calcifications of the Achilles tendon using an open surgical approach and platelet rich plasma (PRP) membranes as a local adjuvant. Methods: The study retrospectively evaluated patients with Haglund syndrome treated with a direct posterior access, Achilles tendon split, bursectomy, resection of the heel deformity and topical administration of PRP membranes. After surgery, a standardized rehabilitation protocol was performed. The preoperative and postoperative functionalities of the foot and ankle were assessed using the American Orthopaedic Foot & Ankle Society (AOFAS) score. Intraoperative and postoperative complications were recorded. Results: Twenty consecutive patients were included. The mean follow-up was 23 months. No patient had major intraoperative or postoperative complications. After the surgery, the mean AOFAS score increased from 44.1 to 92.0, resulting in a statistically significant increase in patient functionality after the treatment (p=0.001). Conclusion: Our results suggest that an open surgical approach consisting of a combination of bursectomy, resection of the calcaneal deformity, and topical administration of PRP membranes may be effective for the treatment of Haglund's disease.
Keywords: Achilles tendon; AOFAS; Haglund’s syndrome; heel pain; PRP